The Influence of Perceived Organizational Support, Work Environment, and Organizational Commitment on Employee Performance with Organizational Citizenship Behavior as a Mediating Variable at PT Lembaga Keuangan Mikro BKD Mandiri Banyuwangi - Nurananda, Prisa; Mardiana, Tri; Warsiki, A. Y. N. (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study was conducted at PT. Lembaga Keuangan Mikro BKD Mandiri Banyuwangi with the aim of examining the influence of perceived organizational support on employee performance, the influence of work environment on employee performance, the influence of organizational commitment on employee performance, the indirect influence of perceived organizational support on employee performance through organizational citizenship behavior as a mediating variable, the indirect influence of work environment on employee performance through organizational citizenship behavior as a mediating variable, and the indirect influence of organizational commitment on employee performance through organizational citizenship behavior as a mediating variable. This research employed a quantitative method using the SmartPLS 3.0 application through outer model testing, inner model testing, and hypothesis testing. The sample consisted of 88 employees who responded to a questionnaire, and all responses were declared valid and reliable. The results of this study indicate that perceived organizational support has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance, and organizational commitment has a positive and significant effect on employee performance. Furthermore, perceived organizational support has a positive and significant indirect effect on employee performance through organizational citizenship behavior as a mediating variable. Similarly, the work environment and organizational commitment also have positive and significant indirect effects on employee performance through organizational citizenship behavior as a mediating variable.